Bone metastases: an overview - Filipa Macedo; Katia Ladeira; Filipa Pinho; Nadine Saraiva; Nuno Bonito; Luísa Pinto; Francisco Gonçalves (Frontiers Media S.A., 2017)
Bone is a frequent site of metastases and typically indicates a short-term prognosis in cancer patients. Once cancer has spread to the bones it can rarely be cured, but often it can still be treated to slow its growth. The majority of skeletal metastases are due to breast and prostate cancer. Bone metastasis is actually much more common than primary bone cancers, especially in adults. The diagnosis is based on signs, symptoms and imaging. New classes of drugs and new interventions are given a better quality of life to these patients and improved the expectancy of life. It is necessary a multidisciplinary approach to treat patients with bone metastasis. In this paper we review the types, clinical approach and treatment of bone metastases.